Learning taxonomy from the Islamic perspective: implications on curriculum instructions and designs - Abdullah, Norillah; Syed Hassan, Sharifah Sariah; Idris, Rabiu Garba (Global Academic Excellence (M) Sdn Bhd, 2024)
The prominence of the Western taxonomy of learning has resulted in serious epistemological problems and contradicted the Islamic worldview as it aims mainly at the achievement of the material world. Islam, on the other hand, looks into emphasizing a holistic learning taxonomy that does not merely emphasize knowledge of the mind but also includes the knowledge that is essential for the soul. Employing a qualitative method, this paper attempts to explicate the concepts of ilm, hikmah, and tafakkur, and their implications on one’s life, and draw a demarcation between the Islamic and Western concepts of ilm (knowledge) and hikmah (wisdom). Ultimately, this paper proposes the taxonomy of ilm from the Islamic perspective and presents it as an alternative to contemporary Muslim educators and scholars. The findings of the current study highlight the major distinctions between the philosophies and goals of Western and Islamic taxonomies of learning. The multidimensional approach of "adabisation,” which encompasses the moral values of Tauheed-based knowledge, is also discussed